An innovative EPW design using add-on features to meet Malaysian requirements - Alsibai, Mohammed Hayyan; Sharif, Mhd Saeed; Salma, Yaakub; Nurul Nadia, Nor Hamran (IEEE, 2018)
Electric Powered Wheelchair (EPW) is a special Electric Vehicle (EV). It is used by senior citizens, handicapped, disabled, people with mobility impairment or people who have health complaints. Therefore, it is not always safe to use an EPW independently as users are more subject to fatigue, weakness and emergency situations. Due to the special needs of EPW drivers/users, the design of the EPW and its controlling system should fulfill their requirements. This paper proposes a new design for EPW which is suitable for Malaysian community needs. The design takes in consideration the easiness of the independent use, the price reduction and the flexibility in changing the controlling method. A smartphone is used as an add-on controlling option besides to the normal joystick. A health monitoring system which implements Internet of Things (IoT) features is also presented as an add-on device. The EPW system is designed to be extendable and accepts other add-on devices. The system is tested in real modes and it is validated as a real-time system.